2019
DOI: 10.4103/ijpsym.ijpsym_373_18
|View full text |Cite
|
Sign up to set email alerts
|

How does India Decide Insanity Pleas? A Review of High Court Judgments in the Past Decade

Abstract: Background:The Section 84 of the Indian Penal Code (IPC) describes how Indian courts have to deal with ‘the act of an unsound person’. This study was undertaken with the objectives of estimating the success rate of insanity pleas in Indian High Courts and determining the factors associated with the outcome of such insanity pleas.Materials and Methods:The data was collected from the websites of 23 High Courts of India using the keywords ‘insanity’ and ‘mental illness’, and the judgments delivered between 1.1.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The psychiatrists appear in Honorable courts as an expert witness and give evidence but are unaware as to what happens later. I commend the investigators for researching a hitherto underresearched topic in Indian scenario,[ 10 ] relating to insanity pleas. [ 11 ] If an accused has a proof that he was under treatment prior to the crime, the treating psychiatrist is likely to be summoned; in 32 out of 67 cases (47.76%), the treating psychiatrist was asked to appear.…”
Section: Legal Issues In Psychiatric Carementioning
confidence: 99%
“…The psychiatrists appear in Honorable courts as an expert witness and give evidence but are unaware as to what happens later. I commend the investigators for researching a hitherto underresearched topic in Indian scenario,[ 10 ] relating to insanity pleas. [ 11 ] If an accused has a proof that he was under treatment prior to the crime, the treating psychiatrist is likely to be summoned; in 32 out of 67 cases (47.76%), the treating psychiatrist was asked to appear.…”
Section: Legal Issues In Psychiatric Carementioning
confidence: 99%
“…Dcruz et al [1] have questioned the use of Pearson's Chi-square test of independence in our article[2] to determine the association between the trial court and high court judgments on the insanity plea in India. The crux of their argument is that the verdict of the trial court and high court is not independent of each other; they are repeated measures on the same subject and are therefore correlated.…”
mentioning
confidence: 99%
“…Calculating the interobserver agreement between the psychiatrist opinion, verdicts of the trial court and the high court has been suggested as one way of analyzing the data. In our study,[2] we reported that in 32/67 cases, the psychiatrist who was treating the patient prior to the crime was called upon as the expert witness. Mean duration of 14.7 months elapsed between the last visit to the psychiatrist and the occurrence of the crime.…”
mentioning
confidence: 99%
“…They concluded that the “success rate of insanity plea in Indian high courts is a modest 17.6% and, lower court verdict, documentary proof of mental illness and psychiatrist's opinion were associated with the success of insanity pleas”. [1] In this letter, we raise concerns regarding their inferences.…”
mentioning
confidence: 99%
“…An application of McNemar's test with continuity correction for small sample size shows that the proportions of acquittal differed significantly between the trial court (p1 = 9/94) and the high court (p2 = 18/94) (χ2[1] =4.9, P = 0.03). Using the binomial sign test, which is an alternative to the McNemar's test for small samples ( n = 94, K = 18), yields a P value of 0.0001, also indicating a statistically significant difference between the courts.…”
mentioning
confidence: 99%